2014
DOI: 10.1017/jfm.2014.316
|View full text |Cite
|
Sign up to set email alerts
|

Intrusion-generated waves in a linearly stratified fluid

Abstract: We present an experimental and numerical study of the upstream internal wavefield in a channel generated by constant density intrusions propagating into a linearly stratified ambient fluid during the initial phase of translation. Using synthetic schlieren imaging and two-dimensional direct numerical simulations, we quantify this wave motion within the ambient stratified fluid ahead of the advancing front. We show that the height of the neutral buoyancy surface in the ambient fluid determines the vertical modal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…It has been inferred that internal gravity waves do play a significant role in some intrusive flows through stratified fluids, such as in the collapse of a mixed region (Amen & Maxworthy 1980). In other flows, however, such as the lock-release currents of Maurer & Linden (2014), energy loss to gravity waves was observed to have a relatively small effect on the propagation of the intrusion. Ansong & Sutherland (2010) made direct experimental observations of gravity waves generated by the scenario that we consider in this paper, namely a buoyant plume and subsequent radial intrusion into a stratified environment.…”
Section: Shallow-layer Modelmentioning
confidence: 99%
“…It has been inferred that internal gravity waves do play a significant role in some intrusive flows through stratified fluids, such as in the collapse of a mixed region (Amen & Maxworthy 1980). In other flows, however, such as the lock-release currents of Maurer & Linden (2014), energy loss to gravity waves was observed to have a relatively small effect on the propagation of the intrusion. Ansong & Sutherland (2010) made direct experimental observations of gravity waves generated by the scenario that we consider in this paper, namely a buoyant plume and subsequent radial intrusion into a stratified environment.…”
Section: Shallow-layer Modelmentioning
confidence: 99%
“…Possible forcing mechanisms for near‐bottom internal waves include current‐topography interaction (Aghsaee et al, 2010; Bourgault et al, 2011, 2014; Klymak & Moum, 2003), shear flow instability (Apel, 2003; Thorpe, 1975) and gravity current intrusions (Flynn and Sutherland, 2004; Maurer & Linden, 2014). Although we lack the spatial coverage needed to determine the exact location of the wave forcing, the observations indicate that the solibores form midway through a spring tidal cycle when strong flood currents are flowing through the main channel immediately to the west of Mooring GVRD‐S.…”
Section: Discussionmentioning
confidence: 99%
“…A possible aspect inhibiting the excitation of the V1H1 mode is that, although a 12-h periodic onset of the wind exists, its duration is less than one-quarter of the mode period (i.e., ~3h), which is the minimum duration of a wind event leading to the formation of the horizontal baroclinic gradients (Spigel & Imberger, 1980) necessary for the complete excitation of the mode. On the other hand, it has been shown that when internal waves are excited by density currents there is a strong influence of the level of neutral buoyancy of the currents on the relative proportion of energy transferred to the different vertical wave modes (Maurer & Linden, 2014). Although more research is needed to prove it, we suggest that the inhibition of the V1 mode excitation is caused by the currents from the selective withdrawal and the river plume moving between 10 m and 40 m, which is the depth range on what the V1 mode should change the velocity direction (Figure 6d).…”
Section: Discussionmentioning
confidence: 99%